A COMPARATIVE STUDY OF ARTERIAL BLOOD GAS AND VENOUS BLOOD SAMPLES AMONG PATIENTS PRESENTING WITH HIGH-ACUITY TRIAGE SCORES IN THE EMERGENCY DEPARTMENT OF A SELECTED HOSPITAL, BIKANER - Taneja, Nikhil; Arora, Jyoti; Ajmera, Chirag (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Introduction: Arterial blood gas (ABG) analysis is the gold standard for assessing acid-base status and respiratory function in critically ill patients, though it carries risks of vascular injury and infection from repeated sampling. Venous blood gas (VBG) analysis, requiring fewer punctures, is safer for patients and providers, and often practical when central catheters are present. Peripheral VBG sampling may offer a suitable alternative, providing similar parameters including electrolytes, lactate, and hemoglobin. Methodology: A quantitative, comparative cross-sectional study design will assess the concordance between arterial and venous blood gas values among patients presenting with ATS 1 and ATS 2 triage scores in the Emergency Ward at Jeevan Raksha Hospital, Bikaner. Consecutive sampling will recruit. Patients refusing consent or presenting with venous blood gas samples will be excluded. Blood samples will be simultaneously collected and analyzed. Data analysis will utilize SPSS version 11.5, employing paired Student’s t-tests for correlation. The study duration will be one year following ethical clearance. Result: The study enrolled 300 patients (Female: 57.3%; Male: 42.7%). The most common diagnoses included COPD exacerbation (22%), CKD with pulmonary edema (13.3%), sepsis (9.3%), pneumonia (8.3%), and poisoning (8%). Blood glucose levels from ABG analyzers were significantly higher than auto-analyzers (mean difference: 11.91 mg/dl, p=0.000). Sodium (mean difference: 4.82 mmol/L, p=0.000) and potassium (mean difference: 0.60 mmol/L, p=0.000) results also showed significant differences, indicating non-interchangeability without correction factors. Hemoglobin levels were clinically comparable (mean difference: 0.12 g/dl, p=0.031), thus interchangeable for clinical practice. Conclusion: Na⁺ and K⁺ values obtained via ABG and auto-analyzer differ significantly and aren’t interchangeable clinically per USCLIA guidelines, highlighting the need for institution-specific correction factors to prevent misdiagnosis. However, Hemoglobin and Random Blood Sugar values showed acceptable agreement. Correction factors identified were Na⁺ (4.82 mmol/L), K⁺ (0.60 mmol/L), Hemoglobin (0.12 g/dl), and Random glucose (11.91 mg/L).